New Insights Into Cyclone Impacts on Sea Ice in the Atlantic Sector of the Arctic Ocean in Winter. Issue 22 (21st November 2022) - Aue, Lars; Vihma, Timo; Uotila, Petteri; Rinke, Annette
Abstract: Based on the ERA5 reanalysis, we report on statistically significant impacts of transient cyclones on sea ice concentration (SIC) in the Atlantic sector of the Arctic Ocean in winter under "New Arctic" conditions (2000–2020). This includes a pattern of reduced SIC prior to and during cyclones for the whole study domain, while a regional difference between increased SIC in the Barents Sea and reduced SIC in the Greenland Sea is found as the net effect from 3 days prior to 5 days after the cyclone passage. Generally, locally low to medium SIC conditions combined with intense cyclones drive highest SIC changes. There are indications that both thermodynamic and dynamic effects contribute to the SIC changes, but a detailed quantification is required in future research. We provide evidence that cyclone impacts on SIC have amplified compared to the "Old Arctic" (1979–1999), particularly in the Barents Sea. Plain Language Summary: We analyze how storms impact the sea ice cover in the Atlantic part of the Arctic Ocean in winter. To capture the current state of the Arctic, we focus on the last two decades (2000–2020). A few days prior to the arrival of a storm at a certain location, the sea ice concentration (SIC) at that location starts to decrease and is reduced most during the day of the storm. After the storm has passed over, the SIC increases again, but only for the Barents Sea, not for the Greenland Sea, where the sea ice remains reduced for at least 1 week. Generally, the impact of storms on sea ice is strongest during intense events and at locations with a broken sea ice cover. During the storm events, the ice cover is modified by different mechanisms, by wind driven ice movement and deformation, as well as by changes in the surface heating, which affect ice growth and melt. Comparing the impact of storms on sea ice for the last two decades with results for a previous period (1979–1999) shows that the impact of storms got stronger recently, particularly in the Barents Sea. Key Points: Cyclones cause an anomalous sea ice concentration (SIC) decrease in the Greenland Sea and an anomalous increase in the Barents Sea in winter Intense cyclones combined with locally low to medium SIC leads to the strongest impacts on sea ice Cyclone impacts on sea ice have intensified under "New Arctic" conditions, particularly during the last decade in the Barents Sea